RP-HPLC method for simultaneous estimation of amlodipine and metoprolol in tablet formulation - Chitlange, Sohan S; Imran, Mohammed; Sakarkar1, Dinesh M (Asian Journal of Pharmaceutics (AJP), 2014)
Areverse phase high performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of amlodipine and metoprolol in marketed formulation is developed. The determination was carried out on a Kromasil C18 (250 x 4.6 mm, 5 μm) column using a mobile phase of 0.02 M phosphate buffer solution: acetonitrile (70:30v/v, pH 3.0). The flow rate was 1.0ml/min with detection at 221 nm. The retention time for amlodipine was 2.57 min and for metoprolol 4.49 min. Amlodipine and metoprolol showed a linear response in the concentration range of 10-110 μg/ml. The correlation co-efficient (‘r’ value) for amlodipine and metoprolol was 0.9991 and 0.9992, respectively. The results of analysis have been validated statistically and by recovery studies. The percentage recoveries obtained for amlodipine and metoprolol ranges from 100.04 to 100.57%.